Age-dependent gait abnormalities in mice lacking the Rnf170 gene linked to human autosomal-dominant sensory ataxia. (3rd October 2015) - Kim, Youngsoo; Kim, Seong Hun; Kim, Kook Hwan; Chae, Sujin; Kim, Chanki; Kim, Jeongjin; Shin, Hee-Sup; Lee, Myung-Shik; Kim, Daesoo
Abstract : Really interesting new gene (RING) finger protein 170 (RNF170) is an E3 ubiquitin ligase known to mediate ubiquitination-dependent degradation of type-I inositol 1, 4, 5-trisphosphate receptors (ITPR1). It has recently been demonstrated that a point mutation of RNF170 gene is linked with autosomal-dominant sensory ataxia (ADSA), which is characterized by an age-dependent increase of walking abnormalities, a rare genetic disorder reported in only two families. Although this mutant allele is known to be dominant, the functional identity thereof has not been clearly established. Here, we generated mice lacking Rnf170 ( Rnf170 −/− ) to evaluate the effect of its loss of function in vivo . Remarkably, Rnf170 −/− mice began to develop gait abnormalities in old age (12 months) in the form of asynchronous stepping between diagonal limb pairs with a fixed step sequence during locomotion, while age-matched wild-type mice showed stable gait patterns using several step sequence repertoires. As reported in ADSA patients, they also showed a reduced sensitivity for proprioception and thermal nociception. Protein blot analysis revealed that the amount of Itpr1 protein was significantly elevated in the cerebellum and spinal cord but intact in the cerebral cortex in Rnf170 −/− mice. These results suggest that the loss of Rnf170 gene function mediates ADSA-associated phenotypes and this gives insights on the cure of patients with ADSA and other age-dependent walking abnormalities.